Design And Characterization On Piezoelectric Cantilever As A Self-Powered Accelerometer - Bong, Yu Jing (2016)
Piezoelectric cantilever working on direct piezoelectric effect has shown promising applications as a sensor as well as a micro-power generator depending on the amount of stress that is applied on the piezoelectric material at different range of frequencies. In this research, a self-powered accelerometer that consists of a wide-band energy harvesting power generator, a low operating frequency device acceleration sensor, and a signal conditioning circuit is designed. Piezoelectric cantilevers are being used in this research as a sensor to measure the vibration acceleration level and at the same time as a generator to power up the amplifier circuit. This research includes characterize the frequency response of the piezoelectric cantilever by altering its effective mass and length, design the selfpowered accelerometer system, and lastly verify the output of the self-powered system with battery powered system. The result shows that increasing the effective mass of the cantilever can reduce the resonant frequency of the cantilever, while reducing the effective length of the cantilever would increase the resonant frequency. The designed self-powered accelerometer is able to operate at broadened operating frequency range of 180-310 Hz with acceleration level of not lower than 0.8-g and is able to produce linear output with a sensitivity of 231.28mV/g-level. The piezoelectric generator is able to produced constant voltage output of 1.8V and power output not less than 80μW at operating condition. While for the sensor, signal is successfully amplified at a factor of 3.2 with error deviation less than 15%. The overall result is verified and shows good agreement of 5% error with conventional battery powered accelerometer system and compatible with standard vibration source.